A pragmatic controlled trial to improve the appropriate prescription of drugs in adult outpatients: design and rationale of the EDU.RE.DRUG study. (9th July 2020) - Casula, Manuela; Menditto, Enrica; Galimberti, Federica; Russo, Veronica; Olmastroni, Elena; Scotti, Lorenza; Orlando, Valentina; Corrao, Giovanni; Catapano, Alberico L.; Tragni, Elena
Abstract: Introduction: Pharmacological intervention is an important component of patient care. However, drugs are often inappropriately used. It is necessary for countries to implement strategies to improve the rational use of drugs, including independent information for healthcare professionals and the public, which must be supported by well-trained staff. The primary objectives of the EDU.RE.DRUG (Effectiveness of informative and/or educational interventions aimed at improving the appropriate use of drugs designed for general practitioners and their patients) study are the retrospective evaluation of rates of appropriate prescribing indicators (APIs) and the assessment of the effectiveness of informative and/or educational interventions addressed to general practitioners (GPs) and their patients, aimed at improving prescribing quality and promoting proper drug use. Methods and analysis: This is a prospective, multicentre, open-label, parallel-arm, controlled, pragmatic trial directed to GPs and their patients in two Italian regions (Campania and Lombardy). The study data are retrieved from administrative databases (Demographic, Pharmacy-refill, and Hospitalization databases) containing healthcare information of all beneficiaries of the National Health Service in the Local Health Units (LHUs) involved. According to LHU, the GPs/patients will be assigned to one of the following four intervention arms: (1) intervention on GPs and patients; (2) intervention on GPs; (3) intervention on patients; and (4) no intervention (control). The intervention designed for GPs consists of reports regarding the status of their patients according to the APIs determined at baseline and in two on-line Continuous Medical Education (CME) courses. The intervention designed for patients consists in flyers and posters distributed in GPs ambulatories and community pharmacies, focusing on correct drug use. A set of indicators (such as potential drug–drug interactions, unnecessary duplicate prescriptions, and inappropriate prescriptions in the elderly), adapted to the Italian setting, has been defined to determine inappropriate prescription at baseline and after the intervention phase. The primary outcome was a composite API. Ethics and dissemination: The study was approved by the Ethics Committee of the University of Milan on 7th June 2017 (code 15/17). The investigators will communicate trial results to stakeholders, collaborators, and participants via appropriate presentations and publications. Registration details: NCT04030468. EudraCT number 2017-002622-21